High-strength porous biomaterials for bone replacement: A strategy to assess the interplay between cell morphology, mechanical properties, bone ingrowth and manufacturing constraints. (15th January 2016) - Arabnejad, Sajad; Burnett Johnston, R.; Pura, Jenny Ann; Singh, Baljinder; Tanzer, Michael; Pasini, Damiano
Graphical abstract: Abstract: High-strength fully porous biomaterials built with additive manufacturing provide an exciting opportunity for load-bearing orthopedic applications. While factors controlling their mechanical and biological response have recently been the subject of intense research, the interplay between mechanical properties, bone ingrowth requirements, and manufacturing constraints, is still unclear. In this paper, we present two high-strength stretch-dominated topologies, the Tetrahedron and the Octet truss, as well as an intuitive visualization method to understand the relationship of cell topology, pore size, porosity with constraints imposed by bone ingrowth requirements and additive manufacturing. 40 samples of selected porosities are fabricated using Selective Laser Melting (SLM), and their morphological deviations resulting from SLM are assessed via micro-CT. Mechanical compression testing is used to obtain stiffness and strength properties, whereas bone ingrowth is assessed in a canine in vivo model at four and eight weeks. The results show that the maximum strength and stiffness ranged from 227.86 ± 10.15 to 31.37 ± 2.19 MPa and 4.58 ± 0.18 to 1.23 ± 0.40 GPa respectively, and the maximum 0.2% offset strength is almost 5 times stronger than that of tantalum foam. For Tetrahedron samples, bone ingrowth after four and eight weeks is 28.6% ± 11.6%, and 41.3% ± 4.3%, while for the Octet truss 35.5% ± 1.9% and 56.9% ± 4.0% respectively. This research is the first to demonstrate the occurrence of bone ingrowth into high-strength porous biomaterials which have higher structural efficiency than current porous biomaterials in the market. Statement of significance: We present two stretch-dominated cell topologies for porous biomaterials that can be used for load-bearing orthopaedic applications, and prove that they encourage bone ingrowth in a canine model. We also introduce an intuitive method to visualize and understand the relationship of cell topology, pore size, porosity with constraints imposed by bone ingrowth requirements and additive manufacturing. We show this strategy helps to gain insight into the interaction of exogenous implant factors and endogenous system factors that can affect the success of load-bearing orthopaedic devices.